Homo sapiens, Chimpanzees and the Enigma of Language - Bermejo-Fenoll, Ambrosio; Panchón-Ruíz, Alfonso; Sánchez del Campo, Francisco (Frontiers in Neuroscience, 2019)
OBJECTIVES The present study explores the hypothesis that the anatomical bone structures of the oral cavity have probably evolved under the influence of language function. The possible changes have been evaluated by comparing two close species essentially differentiated from each other by spoken language. MATERIAL AND METHODS Twenty dry skulls and 20 mandibles of modern Caucasians were compared with 12 dry skulls and 12 mandibles of chimpanzees, with the analysis of 37 variables and the definition of new anatomical parameters. RESULTS A number of highly significant differences were found between humans and chimpanzees. The human temporomandibular joint is comparatively less flat and has a more limited excursive movement range, with structural elements that seem to be lighter. A significant difference is noted in mandibular alveolar vergency and in the internal slope of the mandibular symphysis where the oral cavity’s morphology is modified, thereby increasing the free space for tongue movements in humans. The chin, which is unique to the human species, is quantified through the external slope of the mandibular symphysis with a lesser angle in humans. DISCUSSION It is obvious that there are differences between humans and chimpanzees in the bone morphology of the oral cavity structures. This has been confirmed with the analysis of new variables. Together with other factors (bipedalism, habits and genetics) speech in humans must have played an important role in the aforementioned differences between humans and chimpanzees. The number of mandibular movements involved in speech is far greater than those used in chewing, which must have conditioned the evolution of the oral structures implicated in the development of language. The refinement of the supralaryngeal vocal tract in the human species must have co-evolved with speech fairly recently. The human skull has temporomandibular joints that are comparatively less flat with a more limited movement. There is a greater lingual space and there is also a chin that suggests a muscular stimulant. This leads to the conclusion that, at least in part, speech is behind all these changes, although it is difficult to establish a cause-effect relationship.